The attenuation coefficient and the velocity of thermal and elastic waves in orthorhombic syngony anisotropic media classes 222 and mm2 - Tleukenov, S.; Arinov, E.; Ispulov, N.A.; Seytkhanova, A.K. (Ye.A.Buketov Karaganda State University Publishing house, 2014)
The relevance of research of wave propagation patterns in elastic medium with thermomechanical effect is related to the need to solve theoretical and applied problems of geophysics, seismology, mechanics of composite materials, etc. Bound equations of motion and heat conduction equation differ by complexity and an abundance of physical and mechanical parameters. In connection with this there is a rapidly developing branch of mechanics of deformable solids - thermoelasticity. Within this framework, based on the use of certain physical and mechanical properties of anisotropic medium, we study bound thermal and mechanical fields. In this paper, based on the method of matriciant, we identify the types of dependencies of velocities and attenuation coefficients of bound thermoelastic waves of frequency; high-quality graphics of velocities and damping coefficients of frequency are constructed under changing the parameters of the medium (thermo- mechanical parameters, temperature and thermal conductivity).
222 жəне mm2 класты ромбылық сингониялы анизотропты орталарда жылулық жəне серпімді толқындардың өшу жəне жылдамдық коэффициенттері
Коэффициенты затухания и скорости тепловых и упругих волн в анизотропной среде ромбической сингонии классов 222 и mm2
Keywords: Anisotropic medium; thermoelasticity; Fourier heat equation; harmonic waves; dispersion; periodic structure; matriciant